How did we find out about Pluto? - Asimov, Isaac, 1920-1992.; Kors, Erika W. (New York : Walker and Co., 1991)
Describes the history of Pluto's discovery and what is known and unknown about the planet today.
School Library Journal.
6.7
6.7
5-8.
5-8
Keywords: Pluto (Dwarf planet) -- Juvenile literature; Pluto (Dwarf planet); Pluto (Dwarf planet)